2012
DOI: 10.1021/jp303819e
|View full text |Cite
|
Sign up to set email alerts
|

Database of Small Molecule Thermochemistry for Combustion

Abstract: High-accuracy ab initio thermochemistry is presented for 219 small molecules relevant in combustion chemistry, including many radical, biradical, and triplet species. These values are critical for accurate kinetic modeling. The RQCISD(T)/cc-PV∞QZ//B3LYP/6-311++G(d,p) method was used to compute the electronic energies. A bond additivity correction for this method has been developed to remove systematic errors in the enthalpy calculations, using the Active Thermochemical Tables as reference values. On the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
188
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(203 citation statements)
references
References 60 publications
12
188
3
Order By: Relevance
“…Thermochemical data for molecules and radicals are taken from databases when possible [44][45][46][47], otherwise the thermodynamic functions are estimated using Benson's group additivity concept for thermochemistry [48], using recently proposed group additive values and hydrogen bond increments [41,45,46].…”
Section: Mechanism Constructionmentioning
confidence: 99%
“…Thermochemical data for molecules and radicals are taken from databases when possible [44][45][46][47], otherwise the thermodynamic functions are estimated using Benson's group additivity concept for thermochemistry [48], using recently proposed group additive values and hydrogen bond increments [41,45,46].…”
Section: Mechanism Constructionmentioning
confidence: 99%
“…Much of this data is collated in the NIST database, 1 Active Thermochemical Tables (ATcT), 2 Third Millennium Thermodynamic Database 3 and from numerous experimental and theoretical studies. A recent ab initio study by Goldsmith et al 4 reported thermochemical properties for over 200 combustion relevant species. A study by Verevkin et al 5 collected and critically evaluated experimental data for enthalpies of formation in the liquid phase, enthalpies a) Electronic mail: Author to whom correspondence should be addressed.…”
Section: A Source Of Thermodynamic Propertiesmentioning
confidence: 99%
“…The thermodynamic properties of ethane have been studied extensively 4,11,[13][14][15][16][17][18][19][20][21][22] as shown in Tables I and II Tables III and IV contain literature values for the heat of formation and molar entropy of the ethyl radical. As with most of the species included in this study there are more values available for the heat of formation (Table III) compared to the molar entropy (Table IV).…”
Section: Literature Review Of Thermodynamic Properties Of C1−c4 Smentioning
confidence: 99%
See 2 more Smart Citations